Von der Postmoderne zum practice turn: für ein neues Verständnis des Mensch-Ding-Verhältnisses in der Archäologie - Stockhammer, Philipp (Ethnographisch-archäologische Zeitschrift, 2011)
The epistemological basis of neither processual nor post-processual archaeology has successfully managed to disentangle the complex relationship between humans and things. Both approaches are based on the anthropocentric notion that the relation between humans and things is guided by human intentionality and conceptualized from a human perspective. Within the last few years, material culture studies and workplace studies have demonstrated how things can trigger practices or have an agency of their own. These studies have empirically correlated Pierre Bourdieu’s habitus concept and Bruno Latour’s Actor-Network-Theory. In my view, it is time to extend the practice turn of Culture and Social Anthropology to Archaeology, which should not lead archaeologists to refuse processual and post-processual approaches but to supplement them with the following insights. Humans and things are connected by complex entanglements which are based on a mutual dependence. Humans use things with multiple intentions, but at the same time feel that things move or force them to act. Humans communicate through objects but also with objects in the context of social practices. Subsequently, I demonstrate the transformative power of the human-thing-entanglement within processes of appropriation by drawing on contextual analyses of Aegean-type pottery at the southern Levant in the Late Bronze and Early Iron Ages.